An assessment of Unki Mines’ compliance with Government policies towards beneficiation of the Zimbabwean indigenous people: the case of the indigenization and ZIMASSET policies - Mango, Sharleen Simbiso (Midlands State University, 2018)
Contrary to the expectation that the Indigenization Policies would bring economic empowerment, poverty reduction, rise of employment opportunities and beneficiation of the indigenous people among other things, the vice versa has been largely true in the Zimbabwean context. Thus, a need to determine the extent to which “government interference” has been responsible for the rampant economic dilapidation and perpetual rise in deindustrialization. A juxtaposed class of debate has attributed this deterioration to company failure to accept the role of government in determining community development programs, as such their resistance has attracted harsh penalties that have crippled their operational processes. Therefore, through the use of a triangulated research design, this thesis defines the relationship between Government policies and Corporate Social Responsibility. A simultaneous assessment of Unki Mines’ level of compliance to government policy towards beneficiation of the indigenous people is presented while contextualizing the key success actors that have enabled Unki Mines to thrive where other industries have shut down as a result the same policies. This analysis becomes a springboard upon which recommendations are proffered as to how similar entities can prevail in a similar environment. Purposive and Simple Random Sampling techniques were applied in order to govern the interview and questioner respondents respectively. Data collected was assessed through conventional content analysis in order to describe Unki’s levels of compliance towards the Indigenization and the ZIMASSET Policies. Suffice to say that, the way Unki Mines pays attention to community development and beneficiation, even to the point of drawing internal legislation and assessing progress through audits defies the notions that seek to limit its compliance to government regulation as the core of Unki’s CSI Initiatives. Such dedication can only be accounted for in a system where passion exists. Thus Unki Mines’ CSR is not just a means to retain its Social License to operate, instead it denotes the existence of an excellent compliance mechanism for government policies. Thus it can be concluded that Unki Mines is more than compliant with regards to implementing developmental projects towards beneficiation and empowerment of the indigenous people.